Variations in Preference for Public/Private Care Supports among the Elderly in South-Western Nigeria - Akanbi, Moses Ayokunle (Sahel Journal of Life Sciences FUDMA, 2025)
The study examined variations in preference for Public/Private care Supports among the Elderly in South-Western Nigeria. The data for this study were extracted from a 2012 elderly survey dataset. The data were analyzed using descriptive and inferential (one-way ANOVA) statistical techniques. The major findings indicate that age, education, marital status, marriage-type, employment, religion, ethnicity, and means of livelihood and usual place of residence have apparent variations in low-preferences for public/private care-supports in the study locations. The study concludes that: marital status (p=0.026), religious affiliation (p=0.027), and means of livelihood (p=0.015) are significant socio-demographic variables of respondents that indicate preference for public/private care supports. The study recommends that public/private old people’s home care which can be community-based in order to take care of the elderly in extended family should be considered as a desirable social institution any time from now in South-western Nigeria.